Clinico-epidemiological study of role of patch test in hand eczema - Hogade, Ashok S.; Anusha, P. (International Journal of Research in Dermatology, 2019)
Background: Hand eczema is a common distressing condition in different occupational groups caused by various endogenous and exogenous factors. It appears to be the most common occupational skin disease, comprising 80% or more of all occupational contact dermatitis. Patch test at present is the only scientific method to diagnose the contact allergen and in subsequent management of patient. Methods: An observational study of patch test was conducted on 100 patients of hand eczema in the department of DVL, Basaveshwara Teaching and General Hospital, Kalaburagi. After detailed history and complete examination, patch testing was done using Indian Standard Series and graded by International Contact Dermatitis Research Group criteria at 48 hours and 72 hours. Results: Out of 100 patients, there were 28 females and 72 males. The commonest age group seen was 20-40 years followed by 40-60 years. Commonest sensitizers were to potassium dichromate (34%) followed by nickel (18.7%), Parthenium (12.5%), PPD (7.8%), other (26%). Out of 64 patients who were positive, 82.8% were positive to single allergen, 10% to two allergens and 6.2% to multiple allergens. Conclusions: Patch test is considered as gold standard method for diagnosis of allergic contact dermatitis and thus preventing the morbidity of repeated episodes of eczema.